2018
DOI: 10.1155/2018/1869458
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Shear Behavior and Permeability Evolution of Rock Joints with Variable Roughness and Infilling Thickness

Abstract: The mechanical properties and permeability evolution of sand-infilled rock joints during the shear process is an important issue in rock engineering, such as it pertains to hydraulic fractures filled with proppant. Shear can disrupt the preexisting hydraulic and mechanical equilibrium conditions, thus affecting fluid flow. In this study, we simulate the shear behavior of rock joints with variable roughness and sand infilling thickness using the discrete element code PFC2D. Rock joint roughness is evaluated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…Other researchers reported that the friction coefficient which is used to describes the sliding friction at microcrack surfaces has important effects on the rock strength and proposed the modified Griffith criterion considering the friction coefficient [32]. The values of the friction coefficient were different along the surface of microcracks, and this value was determined by the extent of wear due to sliding [33][34][35][36]. From this aspect, 9 Geofluids the lower friction coefficient observed in the specimen with higher weathering grades could be attributed to cumulative damage and gradual development of the microcrack coalescence during the weathering process.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Other researchers reported that the friction coefficient which is used to describes the sliding friction at microcrack surfaces has important effects on the rock strength and proposed the modified Griffith criterion considering the friction coefficient [32]. The values of the friction coefficient were different along the surface of microcracks, and this value was determined by the extent of wear due to sliding [33][34][35][36]. From this aspect, 9 Geofluids the lower friction coefficient observed in the specimen with higher weathering grades could be attributed to cumulative damage and gradual development of the microcrack coalescence during the weathering process.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…where σ 1 , σ 3 is the maximum and minimum principal stress, respectively, ϕ is the angle between shear plane and the direction of the maximum principal stress. In this study, the orientation of the principal stresses of dynamic loading on a joint is considered in eight forms which is reflected by the parameters k 1 and k 2 in equation (2). Its relationship with the principal geostatic stress under each stress state is shown in Table 1.…”
Section: Geofluidsmentioning
confidence: 99%
“…An appropriate evaluation of shear behavior of rock joints is vital, for instance, when analyzing the stability of rock slopes, designing excavations in jointed rock, and designing rocksocked piles [1]. A considerable amount of work has been conducted to describe the shear behavior of rock joints [2][3][4][5][6][7][8]. However, in a variety of geomechanical engineering applications, such as rock quarrying, rock drilling, rock excavation, and rock blasting, rock joints may be stressed and failed dynamically [9].…”
Section: Introductionmentioning
confidence: 99%
“…The DEM is widely used in geotechnical engineering, such as slopes, embankments, roads, and rocks [36][37][38][39][40][41][42][43][44][45][46]. In geotechnical engineering, DEM can simulate the discontinuity of soil and rock and reveal the microscopic failure mechanism.…”
Section: Introductionmentioning
confidence: 99%